2012
DOI: 10.1002/uog.10093
|View full text |Cite
|
Sign up to set email alerts
|

Maximal amniotic fluid index as a prognostic factor in pregnancies complicated by polyhydramnios

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
71
4
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 22 publications
(27 reference statements)
9
71
4
2
Order By: Relevance
“…It causes the decrease production of amniotic fluid by increase absorption of fluid by lungs, reducing the urine output and also impairs the prostaglandin mediated response of renal vasculature 7,10,11 . The frequency of polyhydramnios was 1.7% in our study which corresponds with the other study mentioned in literature which showed the incidence of 1-2% respectively [2][3][4][5][6] . The causes of polyhydramnios in our study was mainly idiopathic which was similar to study performed by Maymon et al 12 , Tariq S et al 13 and Panting Kemp et al 14 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It causes the decrease production of amniotic fluid by increase absorption of fluid by lungs, reducing the urine output and also impairs the prostaglandin mediated response of renal vasculature 7,10,11 . The frequency of polyhydramnios was 1.7% in our study which corresponds with the other study mentioned in literature which showed the incidence of 1-2% respectively [2][3][4][5][6] . The causes of polyhydramnios in our study was mainly idiopathic which was similar to study performed by Maymon et al 12 , Tariq S et al 13 and Panting Kemp et al 14 .…”
Section: Discussionsupporting
confidence: 90%
“…Polyhydramnios is one of the dreaded complication in obstetric practice, as it affects not only mother but also the fetus. The overall incidence is 1-2% [2][3][4][5][6] . It causes maternal complications like antepartum hemorrhage, respiratory embarrassment, abnormal presentation, uterine dysfunction and also postpartum hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known, that polyhydramnios is associated with the increased risk of different fetal congenital anomalies [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…It seems that not only the finding of polyhydramnios, but also the value of AFI have a significant effect on a fetal and neonatal outcome, including the frequency of birth defects [3,4]. Congenital anomalies were most frequently found in pregnancies complicated by severe polyhydramnios [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation